Answer:
Reduce the mass of the earth to one-fourth its normal value.
Reduce the mass of the sun to one-fourth its normal value.
Reduce the mass of the earth to one-half its normal value and the mass of the sun to one-half its normal value.
Step-by-step explanation:
Every particle in the universe attracts any other particle with a force that is directly proportional to the product of its masses and inversely proportional to the square of the distance between them. So, in this case we have:
![F=(Gm_Em_S)/(d^2)](https://img.qammunity.org/2021/formulas/physics/college/2qkefnbyuocdy8oobkhpt3ase1synvd0of.png)
If
:
![F'=(Gm'_Em_S)/(d^2)\\F'=(G((m_E)/(4))m_S)/(d^2)\\F'=(1)/(4)(Gm_Em_S)/(d^2)\\F'=(1)/(4)F](https://img.qammunity.org/2021/formulas/physics/college/a0ob6i8sgfo92er7krq063zc8sykkddue0.png)
If
![m'_S=(m_S)/(4)](https://img.qammunity.org/2021/formulas/physics/college/ph4rav1klwh8q6wzwrnyihsbdhashnc9ep.png)
![F'=(Gm_Em'_S)/(d^2)\\F'=(Gm_E((m_S)/(4)))/(d^2)\\F'=(1)/(4)(Gm_Em_S)/(d^2)\\F'=(1)/(4)F](https://img.qammunity.org/2021/formulas/physics/college/zphah26uee7t22kto5lftk2vo7l5vg4ezz.png)
If
and
:
![F'=(Gm'_Em'_S)/(d^2)\\F'=(G((m_E)/(2))((m_S)/(2)))/(d^2)\\F'=(1)/(4)(Gm_Em_S)/(d^2)\\F'=(1)/(4)F](https://img.qammunity.org/2021/formulas/physics/college/gpo8e28c5i4h72aovagvhu912hf4u9xddb.png)